MENGGALI POTENSI MAHASISWA MELALUI PENDEKATAN STEM UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH DAN KREATIVITAS DALAM PEMBELAJARAN MEKANIKA - Asshagab, Siti Mutiaraningsih; Galib, La Maronta; Ledang, Irwan; Halmuniati; Jamdin, Zamrin (CAHAYA: Journal of Research on Science Education, 2024)
This study aims to examine the effectiveness of applying the STEM (science, technology, engineering, and mathematics) approach to mechanics education to enhance problem-solving skills and creativity among students. The focus of this research is on third-semester students of the Tadris IPA study program during the 2023/2024 academic year. Using the classroom action research (CAR) method, the STEM approach was implemented through small projects and integrated experiments involving fundamental concepts of mechanics, such as kinematics and dynamics. The research was conducted in two cycles, each followed by evaluation and reflection to improve the learning process. The results showed significant improvements in both measured skills. In the first cycle, the average problem-solving skills score was 65.8, and creativity was 68.5. In the second cycle, problem-solving skills reached 85.4, while creativity improved to 88.2. These findings suggest that the application of the STEM approach in mechanics education can enhance critical thinking, problem-solving, and creativity in students. This study concludes that the use of the STEM approach in mechanics education is an effective method to support the development of essential skills in higher education, particularly in the fields of science and technology.